Answer: The value of
is
.
Step-by-step explanation:
Given: ![f(x) = 4x^2 \text { and } g(x) = x+1](https://tex.z-dn.net/?f=f%28x%29%20%3D%204x%5E2%20%5Ctext%20%7B%20and%20%7D%20g%28x%29%20%3D%20x%2B1)
To find: ![(f_\circ g)(x)](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%28x%29)
As we know it is composition function which means that g(x) function is in f(x) function.
So we have
![(f_\circ g) (x) = f[g(x)]](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%20%28x%29%20%3D%20%20f%5Bg%28x%29%5D)
![\Rightarrow( f_\circ g)(x)= f(g(x)) = 4(g(x))^2](https://tex.z-dn.net/?f=%5CRightarrow%28%20f_%5Ccirc%20g%29%28x%29%3D%20f%28g%28x%29%29%20%3D%204%28g%28x%29%29%5E2)
Now substitute the value of g(x) we get
![(f_\circ g)(x)= 4(x+1)^2](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%28x%29%3D%204%28x%2B1%29%5E2)
Hence, the value of
is
.
26+26=52 which is the side lengths.
116-52=64 which is the other side lengths together. So one side length 32. 32+32+26+26=116
Answer:
The two numbers are 10 and 6.
Step-by-step explanation:
Let's begin by calling these two numbers x and y, and setting up a system of equations.
x-y=4
x*y=60
Now, you can rearrange the first equation to find the value of x expressed through y.
x=y+4
Now, you can substitute this into the second equation.
(y+4)*y=60
y^2+4y=60
y^2+4y-60=0
(y-6)(y+10)=0
y=6
x=6+4=10
Hope this helps!
The answer is D because you would multiply 3 * 6 and 3 * r, getting you 18+3r